Technologies and multi-barrier systems for sustainable groundwater recharge and irrigation - Besancon, Axelle (Cranfield University, 2010)
Managed aquifer recharge (MAR) consists of artificially replenishing groundwater to facilitate reuse and/or the associated environmental benefits. Meanwhile, soil aquifer treatment (SAT) is a process of geo-purification designed and operated to improve the quality of the infiltrating water and is thus a type of MAR. SAT consists of a basin operating under rotation of drying and wetting periods. Often, SAT involves water of impaired quality applied onto soil and consequently it implies various risks of health, geochemical and physical nature with difficult or irreversible remediation. To study the effect of pre-treatment on SAT a pilot plant including conventional activated sludge (CAS), a membrane bioreactor (MBR), tertiary and secondary vertical flow reed beds (VFRB) and SAT soil columns. The sludge retention time (SRT) in the CAS and MBR processes was changed every 6 months to look at the impact of SRT on SAT. Each unit and treatment train effluent was characterised to determine the impact of effluent quality on SAT performance. This study showed that tertiary VFRB, especially when fed with MBR effluent, was the best option for SAT and irrigation reuse as it provided the best compliance with reuse standards and the best fertilisation potential. However, long-term clogging occurred in SAT after tertiary VFRB, suggesting the need for a longer resting period or shorter wetting period. This study also highlighted the importance of total suspended solids (TSS) content for SAT removal mechanisms and infiltration rate. In particular, SAT fed with high TSS content effluent was susceptible to temperature variation. Hence the duration of wetting and flooding periods should be adapted according to the season. Further, variation in SRT only indirectly affected pollutants removal by the system including CAS treatment set up at 6 d SRT where the N compounds balance was favourable to an autotrophic N removal.
Keywords: Soil aquifer treatment; MBR; activated sludge; reed bed; sludge retention time; phosphorus; metal